Digital Business Model Innovation and Its Impact on Competitive Advantage: Evidence from Indonesian Tech Startups - Kosasih, Nico (TechTalent & Business Review, 2025)
Digital business model innovation (DBMI) has emerged as a critical determinant of competitive advantage for Indonesian technology startups in an increasingly competitive market landscape. This study examines the mechanisms through which DBMI influences competitive advantage among Indonesian tech startups, analyzing both internal and external factors that contribute to their success. Using a systematic literature review approach, we synthesized findings from 25 studies focusing on Indonesian digital startups across various sectors including fintech, edutech, e-commerce, and healthtech. Our analysis reveals that DBMI significantly enhances competitive advantage through four key mechanisms: capability reconfiguration, digital technology adoption, platform ecosystem dynamics, and dynamic capabilities development. The findings indicate that startups implementing disruptive business models demonstrate superior scalability and market survival rates. Technology adoption, particularly AI and data analytics, substantially improves operational efficiency and market expansion, leading to increased user growth and revenue generation. However, challenges such as cybersecurity threats, digital gaps, and intense marketing competition remain significant barriers. Government policy support and conducive digital ecosystems are crucial for enabling continuous innovation and global competitiveness. This study contributes to theoretical development by extending the Resource-Based View (RBV) and Dynamic Capabilities Theory within the digital context, specifically demonstrating how DBMI mechanisms create sustainable competitive advantages through capability reconfiguration and ecosystem orchestration. The findings provide strategic insights into capability development pathways, policy intervention points, and ecosystem design principles for entrepreneurs, policymakers, and investors in Indonesia's digital economy.